Facilitating Palliative Care Referrals in the Intensive Care Unit. Issue 6 (November 2015) - Jenko, Mimi; Adams, Judith A.; Johnson, Constance M.; Thompson, Julie A.; Bailey, Donald E.
<x xml:space="preserve">Abstract</x> Background: Palliative care in intensive care units (ICUs) reduces costs and improves outcomes yet is consistently underused; studies suggest that screening tools increase the use of palliative services. Aims: This project piloted the use of the Palliative Performance Scale, version 2 (PPSv2), as a trigger for palliative care referrals in a 12-bed medical ICU. Methods: Using a preintervention-postintervention design, the authors measured the effect of the intervention on nurses' comfort and knowledge in assessing palliative care needs, number of palliative care referrals, and number of days between ICU admission and palliative care referral. The authors also measured uptake of the scale over 12 weeks of implementation and asked nurses to share their thoughts about using the PPSv2. Results: Over 610 observations, the rate of uptake increased over time and use of the scale ranged from 24.2% to 85.6%. The nurses' (n = 26) comfort with palliative care issues increased from preintervention to postintervention, albeit not significantly. Knowledge items did not change. There was a 110% increase in the number of palliative care referrals between preintervention and postintervention and a nearly 1-day decrease in the number of days between medical ICU admission and palliative care referral; this reduction was not statistically significant. A majority of nurses (n = 22 [84.5%]) voted to retain the PPSv2 as an official process of care, stating that the tool facilitated assessment of patient needs that might have been previously overlooked. Conclusion: Data suggest that the PPSv2 was well received by the bedside nurses and changed practice patterns with regard to facilitating palliative care services.